Deriving a conceptual framework for a formative evaluation of the city of Johannesburg : ‘separaton of powers pilot project. - Chikwema, S.; Wotela, K. (My University, 2016)
Oversight and accountability of the executive to the legislature are cardinal to good governance and ultimately democracy and political development. Conflating legislative and executive functions limits oversight, effectiveness of governance arrangements, accountability, and public participation. The Department of Cooperative Governance and Traditional Affairs (COGTA) has stressed that governance and democracy at local level is ‘in distress’ because of inadequate accountability measures and a lack of a clear separation between the legislature and the executive. To counter the latter and improve governance, the City of Johannesburg provided for institutional arrangements that separate executive and legislative functions of Council in 2006. However, after implementing this governance model, we are not certain if separating legislative and executive functions of a municipal council improves governance at municipality level. This research intends to assess if this initiative can improve local level governance. Therefore, the focus of this article is on developing a conceptual framework for such a formative assessment. The article applies these frameworks to collect, process, and analyse data as well as interpret the empirical results.
Published in: Journal of Public Administration and Development Alternatives. Vol. 1, No.1, July 2016, 150-170.
Keywords: Governance